State Dependence in a Multi-state Model of Employment Dynamics. - Prowse, V (Nuffield College (University of Oxford), 2005)
A multinomial choice framework is used to investigate the nature of women`s transitions between full-time employment, part-time employment and non-employment. The stochastic framework allows time varying and time invariant unobserved preferences, and also controls for the possible endogenity of education, fertility and non-labor income. Significant positive true state dependence is found in both full-time employment. This finding is robust to the specification of unobserved preferences. The results are used to assess the dynamic effects of three temporary wage subsidies. All three policies have substantial effects on employment behavior for up to 6 years. However, obtaining a permanent increase in employment requires sustained or repeated interventions.